Business Performance in Informal Street Trading Enterprises in Nigeria: Does Gender Matter? - Busayo ADEROUNMU; Ebenezer BOWALE; Isaiah OLURINOLA (Communications of International Proceedings, 2021)
The study examined the effect of gender on business performance using a survey (backed up with focus group discussion) carried out among street traders in four purposively selected cities representing the North, South and Eastern parts of Nigeria in 2011.  A total of 1,613 female and 2,260 male street traders were interviewed across the four selected cities in Nigeria. For this particular study, we examined the driving factors for informal sector entrepreneurship among the male and female business owners in the study. The OLS result showed that total sales, level of present capital, educational attainment, age of respondent, positively influences business performance among street traders while gender (male) nature of trading and Lagos negatively influences business performance.
Keywords: Entrepreneurship; Gender; Street Trading; Informal Economy; Nigeria.